Exploring the Critical Role of Water in Regenerative Agriculture; Building Promises and Avoiding Pitfalls - Lankford, Bruce; Orr, Stuart (Frontiers in Sustainable Food Systems, 2022)
This article seeks greater clarity in the connections between water and regenerative agriculture (RA). We first review existing soil/water knowledge and argue that desired ‘RA and water’ outcomes depend on the management and optimal levels of two key soil properties; readily available moisture and infiltration rate. Secondly, we hypothesize these help define a range of RA beneficial outcomes or ‘promises’, such as improved vegetative growth, reduced risk of erosive runoff, higher soil organic matter content and biological fertility, easier irrigation management, resilience to drought, better water filtration and less variable streamflow hydrology. Thirdly we show that by not fully understanding water’s multiple roles for achieving desired RA outcomes, risks, contradictions and ‘pitfalls’ can arise. With these three parts we observe that carefully explained and quantified roles of water in the existing RA literature are often missing, neglected, over-generalized or poorly explained. We also suggest that narratives and terms (e.g. ‘net zero’ or ‘net positive’) for describing the benefits and aims of RA and water can lack context and situational fit, or are misleading and incorrect. Cautions also apply to water quantities additionally required for soil regeneration activities, recognizing stiff competition for scarce river basin water and its allocation. How necessary quantities overlap with local and catchment policies for water allocations and hydrology, incorporating farmers’ views and choices and informed by field, farm and system water accounting, are critical to successful agricultural practices including those that are ‘regenerative’. Accordingly, we suggest that scientists and decisions-makers should more thoroughly interrogate how ‘RA and water’ is being analyzed so that relevant policies develop its promises whilst avoiding pitfalls.